Rock magnetic analysis for samples of the Napier Complex in the Mt. Riiser-Larsen area, East Antarctica - Ishikawa, Naoto; Funaki, Minoru (National Institute of Polar Research, 1998)
P(論文) Samples collected at eight sites from granulites of the Archean Napier Complex and dolente dikes intruding the complex in the Mt. Riiser-Larsen area, East Antarctica, were analyzed rock-magnetically in order to assess the stability of their natural remanent magnetizations (NRMs). Results of isothermal remanence acquisition experiments and hysteresis measurements indicate the presence of magnetite in the pseudo-single to multi domain size, which is consistent with N. ISHIKAWA and M. FUNAKI (Proc. NIPR Symp. Antarct. Geosci., 10, 79, 1997). Stable magnetic components carried by fine-grained magnetites were isolated from some sites. Samples with such components may have a mixture of magnetites with different grain sizes although the effect of the mixing was not clearly observed. Heavily-deformed samples were found to be magnetically amsotropic, while magnetic fabrics of less-deformed samples indicate the possibility that the fabrics are of primary origin. The high-stability magnetic components from the less-deformed dolente samples of one site with primary magnetic fabrics may be of primary remanence acquired in the emplacement of the dike at 0.8-1.0Ga. departmental bulletin paper